The civil engineering handbook - Chen, W. F. (CRC Press, 1995)
This book is organized into eight sections, covering the eight traditional areas of civil engineering: * construction engineering * environmental engineering * geotechnical engineering * hydraulic engineering * materials engineering * structural engineering * surveying engineering * transportation engineering. It contains many formulas and tables that give immediate answers to questions arising from practical work. It also contains a brief description of the essential elements of each subject